Estudo das propriedades antimicrobianas de filmes de nanocelulose e nanopartículas de prata - Medeiros, Cassiano Heitor Santos de (Universidade Federal de São Carlos, 2019)
Silver is an element with widely recognized bactericidal activity. Its use in the modification of materials has been studied for decades and its use goes through different forms of incorporation in the matrices of interest, such as surgical instruments, prostheses, heart valves, tissues, personal hygiene products and food containers. The present work intends to analyze the antimicrobial performance aggregated in nanocellulose films containing silver nanoparticles (AgNPs). Nanocomposite films were produced through a suspension of vegetable nanocellulose and AgNPs synthesized using sodium citrate as reductant and stabilizer, the technique is based on the adaptation of a filtration system to the vacuum and subsequent drying in a system of own production. The characterization of the nanocomposite films in relation to their antimicrobial properties was performed by means of the disc diffusion technique in triplicate of “test” samples incubated for 24 hours at 35 ºC in Petri dishes cultivated with the strains of microorganisms Staphylococcus aureus and Pseudomonas aeruginosa, present in outbreaks of hospital infection. UV-Vis analyzes were conducted on the aqueous suspension of AgNPs indicating the presence of particles ranging in size from 35 to 50 nm. The average thickness of the films removed from the drying system at 3 days and 7 days of curing was 112 ± 7 μm and 93 ± 5 μm, respectively. Results of silver atomic concentration had a mean value of 0.18 ± 0.07% with maximum concentration of 0.29 ± 0.09%. After measuring the inhibition halos formed, with an average value of 7.2 ± 0.2 mm against S. aureus and 7.7 ± 0.3 mm against P. aeruginosa, it was possible to observe successfully the antimicrobial effect in NC-AgNPs films obtained. Other techniques such as scanning electron microscopy, contact angle and infrared spectroscopy by attenuated total reflectance were also conducted to determine the morphology, wettability and functional groups characteristic of the films.
Study of the antimicrobial properties of nanocellulose films and silver nanoparticles
Keywords: AgNPs, nanocelulose, deposição por plasma, compósitos, atividade antimicrobiana; AgNPs, nanocelulosa, deposición de plasma, compuestos, actividad antimicrobiana; AgNPs, nanocellulose, plasma deposition, composites, antimicrobial activity; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES